The using of genetic markers as a possibility of predicting the rate of progress of liver fibrosis in patients with chronic hepatitis B - К.М. Usychenko (Medičnì Perspektivi)
According to recent WHO estimates, chronic HBV infection is one of the leading causes of death and disability in patients with infectious diseases. From 780 thousand to 1 million deaths are annually recorded in the world as a result of cirrhosis of the liver and hepatocellular carcinoma. Pathogenetic features of the course and outcomes of chronic hepatitis B are determined by the immunological, genetic factors of the host, as well as the molecular biological structure of the virus. The aim of the work was to study the interaction of polymorphic loci of the cytokine genes SMAD 7 (rs4939827), TNFα (rs1800620), IL-10 (rs1800896), IL-4 (rs2243250) and the degree of structural changes in the liver based on the non-invasive Fibrotest technique in patients with chronic hepatitis B as part of a search for possible predictors of predisposition to the rapid progression of liver fibrosis. The study included 82 patients with chronic hepatitis B. Assessment of morphological changes (stage of fibrosis) was carried out by the method of non-invasive diagnosis of FibroScan, which is an alternative to puncture biopsy of the liver. It has been suggested that homozygous alleles СС IL-4 (rs2243250), GG TNFα (rs1800620), СС SMAD family member 7 (rs4939827) have a protective effect on the course of chronic hepatitis B, as these variants of allelic polymorphism of cytokine genes were found mainly in patients with CHB with a degree of fibrosis F0-F1. The heterozygous genotypes СТ IL-4 (rs2243250) and GA TNFα (rs1800620), the mutant homozygous ТТ SMAD family member 7 (rs4939827) have a profibrotic effect on the course of chronic hepatitis B, as they are found mainly in patients with chronic hepatitis B with degree of fibrosis F3. The established relationship between the liver fibrosis stage according to the METAVIR scale and the polymorphism of the cytokine genes SMAD 7 (rs4939827), TNFα (rs1800620) and IL-4 (rs2243250) made it possible to create a prognostic scale for assessing the individual risk of rapid progression of liver fibrosis. The proposed scale, due to a comprehensive assessment of the polymorphism of cytokine gene alleles and the stage of liver fibrosis using the METAVIR scale, makes it possible to carry out an individual assessment of the risk of progression of chronic hepatitis and, possibly, draw up a personalized treatment plan for the patient. Coding of the studied polymorphisms and subsequent counting can be automated, which does not require significant financial investments. The possibilities of the prognostic scale are proven on the example of a group of patients who received the antifibrotic agent bicyclol in comparison with the control group.